Challenges to decision-making processes in the national HTA agency in Brazil: operational procedures, evidence use and recommendations - Tania Yuka Yuba; Hillegonda Maria Dutilh Novaes; Patrícia Coelho de Soárez (BMC, 2018)
Abstract Background The quality of the evidence used in health technology assessment (HTA) agency reports has been considered essential for decision-making processes and their legitimacy. In Brazil, CONITEC is the agency responsible for defining data mandatory for the submission of proposals for the incorporation of new technologies. The objective of this study was to analyse CONITEC recommendation reports, the type of scientific evidence used in them and their compliance with operational procedures. Methods This is a descriptive study based on CONITEC official reports from July 2012 through December 2016. Data were collected with a specific extraction form and analysed using descriptive statistics. Results We evaluated 199 CONITEC recommendation reports. The annual number of reports increased during the study period. The absolute annual number of new technologies incorporated in 2013 (n = 24) was similar to that observed for 2014 (n = 24) and 2015 (n = 22), decreasing in 2016 (n = 13). The type of technology most frequently evaluated was 'drugs' (68.3%), followed by 'procedures' (20.1%). Overall, 117 (58.8%) reports were internal demands, 75 (37.7%) were external demands and 7 (3.5%) were mixed demands. There were differences between internal and external demands in terms of the evidence used in the reports and the decision regarding the recommendation to incorporate the technologies. Among the internal demands, the recommendation to incorporate the new technology was made for 70.9% of the reports, only 9.6% of which included full HTAs. Among the external demands, the incorporation of the new technology was recommended for 17.3% of the reports, 76.9% of which included full HTAs. Of the 101 reports in which incorporation of the new technology was recommended, 88 (87.1%) did not include a full health economic evaluation and ICER calculation. There are compliance difficulties with the recommendations in the CONITEC internal regulations regarding the type and quality of evidence considered in the analysis of recommendation reports. Conclusions The characteristics of the evidence used in recommendation reports and those considered to be mandatory were very different, indicating problems in decision-making processes. There is a need to study, with a broader perspective, the factors that influence the type of evidence used in decision-making processes in order to contribute to the development of better practices and policies.